Data-driven pedestrian simulation - Zhao, Mingbi (2017)
Over the past few years, crowd simulation has been an active research field with an increasing attention from different research areas such as virtual environment, object tracking, computer animation and civil planning. These applications require the synthesized pedestrians to move in a realistic and believable manner, in order to have an excellent user experience or to draw some reliable conclusions based on the simulation results.